Carotid-femoral pulse wave velocity is associated with N-terminal pro-B-type natriuretic peptide level in patients with atrial fibrillation. Issue 1 (27th July 2011) - Chen, Lin Y; Tai, Bee C; Foo, David C; Wong, Raymond C; Adabag, A Selcuk; Benditt, David G; Ling, Lieng H
Abstract : Objective: To determine the extent to which conduit artery stiffness is associated with plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) in patients with atrial fibrillation (AF). Design: Cross-sectional study. Setting: National University Hospital, Singapore. Patients: Cases (n=117) were patients with AF onset <65 years of age without heart failure or structural heart disease. Controls (n=274) were patients without AF who were seen at the general cardiology clinic. Interventions: Transthoracic echocardiography, carotid-femoral pulse wave velocity (CFPWV) measured using applanation tonometry and blood draw for plasma NT-proBNP at enrolment for all patients. Main outcome measures: Plasma NT-proBNP. Results: In patients with AF, CFPWV was associated with NT-proBNP after adjusting for hypertension and factors that were univariately associated with NT-proBNP: age at enrolment, type of AF, body mass index, left ventricular mass index, left atrial volume index, mitral E/E′, mitral deceleration time and use of β-blockers (β=0.234; 95% CI 0.100 to 0.367; p=0.001). In contrast, CFPWV was not associated with NT-proBNP in controls. In patients with AF, the adjusted mean NT-proBNP level in the highest quartile of CFPWV (350 pg/ml; 95% CI 237 to 517 pg/ml) was fivefold higher than the lowest quartile (69 pg/ml; 95% CI 47 to 103 pg/ml) (p=0.001). Conclusions: CFPWV is associated with NT-proBNP level in AF. Since elevated NT-proBNP is a marker of adverse cardiovascular outcomes, arterial stiffness may be associated with worse prognosis in patients with AF.